Multi-Omics Association Reveals the Effects of Intestinal Microbiome–Host Interactions on Fat Deposition in Broilers - Jing, Yang; Yuan, Yuqi; Monson, Melissa; Wang, Peng; Mu, Fang; Zhang, Qi; Na, Wei; Zhang, Ke; Wang, Yuxiang; Leng, Li; Li, Yumao; Luan, Peng; et al. (Frontiers in Microbiology, 2022)
Growing evidence indicates that gut microbiota factors cannot be viewed as independent in the occurrence of obesity. Because the gut microbiome is highly dimensional and complex, studies on interactions between gut microbiome and host in obesity are still rare. To explore the relationship of gut microbiome-host interactions with obesity, we performed multi-omics associations of gut metagenome, intestinal transcriptome and host obesity phenotypes in divergently selected obese-lean-broiler lines. Metagenomic shotgun sequencing generated a total of 450 gigabases of clean data from 80 intestinal segment contents of 20 broilers (10 of each line). The microbiome comparison showed that microbial diversity and composition in duodenum, jejunum, ileum and ceca were altered variously between the lean- and fat-line broilers. We identified 2 jejunal microbes (Escherichia coli and Candidatus Acetothermia bacterium) and 4 cecal microbes (Alistipes sp. CHKCI003, Ruminococcaceae bacterium CPB6, Clostridiales bacterium and Anaeromassilibacillus sp. An200), which were significantly different between the two lines (FDR < 0.05). When comparing functional metagenome, the fat-line broilers had an intensive microbial metabolism in duodenum and jejunum but a degenerative microbial activities in ileum and ceca. mRNA-sequencing identified a total of 1667 differential expressed genes (DEG) in the four intestinal compartments between the two lines (|log2FC| > 1.5 and FDR < 0.05). Multi-omics associations showed that the 14 microbial species with abundances that were significantly related with abdominal fat relevant traits (AFRT) also have significant correlations with 155 AFRT-correlated DEG (P < 0.05). These DEG were mainly involved in lipid metabolism, immune system, transport and catabolism, and cell growth related pathways. The present study constructed a gut microbial gene catalog of the obese-lean-broiler lines. Intestinal transcriptome and metagenome comparison between the two lines identified candidate DEG and differential microbes for obesity, respectively. Multi-omics associations suggests that abdominal fat deposition may be influenced by the interactions of specific gut microbiota abundance and the expression of host genes in the intestinal compartments in which the microbes reside. Our study explored the interactions between gut microbiome and host intestinal gene expression in lean and obese broilers, which may expand knowledge on the relationships between obesity and gut microbiome.